Comparison between Two Molecular Techniques: Nested and Real-Time Polymerase Chain Reaction Targeting 100-kDa Hc Protein for Detection of Histoplasma capsulatum in Environmental Samples (2022)
ABSTRACT: Histoplasmosis, one of the most frequent endemic mycoses in the Americas, is caused by the inhalation of airborne conidia of Histoplasma capsulatum. Better understanding of the distribution of this fungus in the environment is important for the development of appropriate public health measures to prevent human infections. Previously, we used Hc100 nested polymerase chain reaction (PCR) to identify H. capsulatum DNA in 10% of environmental samples in Colombia. Here, we validate a 100-kDa real-time PCR assay for the detection of this fungus in the environment. Using this method, we identified H. capsulatum DNA in 80% of samples of raw organic materials, such as chicken manure, soil from caves, and bird and bat guano, as well as in 62% of samples of organic fertilizer that underwent the composting process. We demonstrated that 100-KDa real-time PCR is a useful tool for environmental surveillance that can be used to identify the potential reservoirs of H. capsulatum and to prevent outbreaks, especially in people with the higher risk of exposure, such as spelunkers, farmers, poultry manure collectors, and anyone who handle organic fertilizers or bat and bird excreta.